Announcement of Retraction - Taylor, Marina (International Journal of Educational Technology and Learning, 2018)
Announcement of Retraction The editorial board announced this article has been retracted on May 9, 2019. If you have any further question, please contact us at: info@scipg.com Title: Assessment of Intercultural Competence as an Outcome of Internationalization in Educational Centers Author: Solmaz Zanganeh International Journal of Educational Technology and Learning ISSN: 2523-0581 Volume and Number: Vol. 2, No. 2, 2018 Pages: 48-53 DOI: 10.20448/2003.22.48.53